Does the attentiveness of NEDs to ESG issues influence corporate sustainability? - Clare, A.; Pinheiro, C. M.; Pozzolo, A. F. (Corporate Social Responsibility and Environmental Management, 2025)
In this paper, our core research question is: do NEDs' ESG attentiveness contribute to corporate sustainability? Being detached from daily management decisions, NEDs are well-positioned to supervise the effort for more sustainable business activities. Indeed, previous empirical research has confirmed that companies that share board directors exhibit superior ESG credentials. Based on individual board characteristics for all FTSE-350 companies listed from 2012 to 2022, our study makes an original contribution to this literature. We find an economically and statistically significant relationship between ESG corporate performance and the presence on a board of NEDs that serve on the boards of other companies that have a strong ESG performance. We make this contribution by proposing and calculating a measure of NED attentiveness. From a corporate governance perspective, our findings underscore the practical influence of specific board capital on corporate ESG performance.